Spendception and AI-Driven Digital Payment Deception: A Literature Review - Fajar Susanto; Bhenu Artha; Sadath M. Nur; Felyanah Dessy Cinthya Putri; Cynta Akya Dinka (Jurnal Riset Manajemen, 2026)
This systematic literature review examines "spendception", the psychological deception of spending more when using digital payments, within the context of recent trends in digital finance from 2020 to 2026. The review synthesizes 42 peer-reviewed studies to identify critical research gaps, analyze the convergence of AI-driven personalization and real-time transaction processing in exacerbating impulsive consumption, and establish the imperative for policymakers and marketing organizations to prioritize consumer protection and digital literacy initiatives. The SLR reveals significant gaps in longitudinal research, neurobiological understanding, regulatory integration, intersectional vulnerability analysis, and intervention mechanisms, gaps essential for developing comprehensive consumer protection frameworks in an increasingly sophisticated fintech ecosystem.